Peasant Social Movements and Agrarian Reform in North Sumatra: A Resource Mobilization Theory Perspective on the Struggle for Land Rights - Linda Elida (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2025)
Agrarian conflict remains one of the most persistent sources of social tension in North Sumatra, where former plantation concessions, transmigration settlements, and customary (adat) territories continue to generate disputes over land rights. This article examines how peasant communities and their allied organizations mobilize resources to sustain their struggle for agrarian reform in the province. Using Resource Mobilization Theory (RMT) as an analytical lens, the study draws on a qualitative literature and documentary review of scholarly publications, policy analyses, and case reports concerning agrarian movements in North Sumatra and comparable regions of Indonesia. The findings show that peasant movements mobilize four interlocking resource types (material, human, moral, and cultural-organizational) channeled through farmer associations, faith-based institutions, non-governmental intermediaries, and broader civil-society coalitions. These movements employ framing strategies, legal advocacy, and contentious collective action to press claims against both state agencies and corporate land users. Structural asymmetries in political and legal resources, however, continue to constrain the movements' bargaining position. The article concludes that sustainable agrarian reform in North Sumatra requires strengthening peasant organizational capacity and more inclusive, multi-stakeholder resource mobilization.